Alice Walker’s discovery of Womanist Zora Neale Hurston: Janie in Their Eyes were Watching God - Orpa, Shanchary Kader (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.